2021
DOI: 10.1371/journal.pone.0248363
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of a mobile phone-based Interactive Voice Response (mIVR) system for monitoring childhood illnesses in a rural district of Ghana: Empirical evidence from the UTAUT model

Abstract: Background The use of a mobile phone-based Interactive Voice Response (mIVR) System for real time monitoring of childhood illnesses provides an opportunity to improve childhood survival and health systems. However, little is known about the factors that facilitate its use. This study sought to identify key determinants and moderators of mIVR system use among caregivers in a rural district of Ghana using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Methods The mIVR system was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The results of the study indicated that the main constructs of UTAUT, PE, and FC significantly influenced the public's intention to adopt telerehabilitation. Some previous studies that have applied the UTAUT model to identify the important factors influencing the use of telemedicine have also established similar results (27)(28)(29). The findings suggested that the individuals' foremost focus when using telerehabilitation remains on whether telerehabilitation can meet their actual rehabilitation needs.…”
Section: Discussionsupporting
confidence: 60%
“…The results of the study indicated that the main constructs of UTAUT, PE, and FC significantly influenced the public's intention to adopt telerehabilitation. Some previous studies that have applied the UTAUT model to identify the important factors influencing the use of telemedicine have also established similar results (27)(28)(29). The findings suggested that the individuals' foremost focus when using telerehabilitation remains on whether telerehabilitation can meet their actual rehabilitation needs.…”
Section: Discussionsupporting
confidence: 60%
“…FC are referred as a predictor of UB of technologies for caregivers. 61,68,85,87 Similarly, Adjei et al 88 found FC and BI positively and significantly related to UB in a study exploring a mobile technology intended to support caregivers.…”
Section: Discussionmentioning
confidence: 92%
“…These results are similar to previous studies, where high BI and FC are the only predictors of UB. 90 We observed that participants of this evaluation wanted to be updated on the care recipients' health and recreational engagement and involved in care coordination and communication with LTC staff. Similarly, during the qualitative phase, participants highlighted that having technologies such as the mSCS could engage more family members in care activities.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A recent survey and qualitative literature on mobile phone–based health interventions in Africa illustrated the differential importance of the UTAUT constructs. A path analysis of UTAUT constructs examined attitudes toward a mobile interactive voice response system for monitoring childhood illness in Ghana and found that performance expectancy, effort expectancy, and social influence were positively associated with behavioral intention to use the technology [ 24 ]. Similarly, a real-world mixed methods acceptability study of an SMS text message–based adherence-monitoring intervention in Uganda concluded that performance expectancy was the key driver of the acceptability of the system [ 9 ].…”
Section: Discussionmentioning
confidence: 99%